Análisis de las aplicaciones tecnológicas en el área de matemática y su relación con las necesidades educativas de estudiantes del siglo XXI - Pineda Sánchez, Paola Nathalí (2022)
The use of technology in education, as a didactic resource, has become a central axis, globalization, the pandemic and social conflicts have given rise to teachers and students see it as a means of communication and school continuity, so it is very important its articulation in the educational process, taking advantage of all the advantages that exist, in order to strengthen and generate new ways to access, build and transmit knowledge. In this context, the objective of the present research was "To analyze the main advantages and disadvantages of technological applications in the mathematics area for Basic Education and their relationship with the educational needs of 21st century students". The research type was documentary, using a qualitative approach with a descriptive study; the methods used were: collection of sources, review, comparison, interpretation, deductive and descriptive; for the collection, organization and analysis of information, the instruments used were cards, electronic page registry and a data matrix. As a result, it is highlighted that there are a variety of advantages that benefit teachers, students and learning, as well as disadvantages that must be considered so that the use of technology does not work against the educational process; It is concluded that the use of technological applications in education, with respect to the subject of mathematics, is fundamental for the motivation and facilitation of learning, which allows improving the quality of education, making students use the knowledge acquired in the needs that arise every day, adjusting to the requirements of today's society; it is also concluded that teacher training, with respect to the use of technological applications, is very important because it allows optimizing time and resources, adjusting to the needs of students. Key words: Technological applications, ICT, educational needs, 21st century students, mathematics area.